Indigenous Knowledge and Medicinal Significance of Seasonal Weeds of District Gujrat, Punjab, Pakistan - Rehman, Abdur; Hussain, Khalid; Nawaz, Khalid; Arshad, Noshia; Iqbal, Iqra; Ali, Syed Saqib; Nazeer, Arifa; Bashir, Zobia; Jafar, Sana; Arif, Usman (Ethnobotany Research and Applications, 2020)
Background: Most of the medicinal plants are available as wild or weeds in the world including Pakistan. It was reported by many researcher that Pakistan is rich with medicinal flora based upon the surveys conducted in the Northern areas but still there are some areas other than Northern parts in Pakistan that has not been studied so far. There is a need to explore the medicinal flora from neglected area where most of the people still rely on local medicinal plants to cure their diseases by means of indigenous knowledge. District Gujrat is among those area that has not been explored to study the medicinal flora. Methods: Surveys were conducted to collect the indigenous knowledge and medicinal significance of seasonal weeds in Gujrat, Punjab, Pakistan in winter 2018 and summer 2019. Information collected through questionnaire and interviews. Results: Weeds have much importance among local inhabitants to cure many diseases as respiratory disorders, kidney and liver disorders, muscle and skeletal disorders, ear, nose and throat problems, dermatological disorders, fever, diabetes, cancer etc. The plant parts and its percentage used by local inhabitants were leaves (58%), fruits (36%), seeds (25%), whole plant (34%), roots (32%), milky latex (1%), flowers (8%) and stem (3%). The most important families were Asteraceae, Poaceae, Fabaceae, Polygonaceae and Solanaceae. Cichorium intybus L. (Asteraceae) had 100% Fidelity Level (FL) value as liver tonic and blood purifier. Highest 0.76 Informant Consensus Factor (ICF) values were noted against stomach, gastric, intestinal and digestive problems. Achyranthes aspera L. (Amaranthaceae) showed the highest Fidelity Level (FL) values that was 93% used gastrointestinal disorders and menstrual pain. Conclusion: It was concluded that the area of Gujrat, Punjab, Pakistan is a rich source of important medicinal weeds that needs to be utilized for useful medicinal purpose. There is need to create awareness among the farmers and local people about the efficacy of weeds.